1999
DOI: 10.1111/j.1471-0307.1999.tb02075.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pasteurization temperature on the physicochemical composition and colour of Murciano‐Granadina goat milk

Abstract: An evaluation of the physicochemical characteristics and colour in Murciano‐Granadina goat milk was carried out on several samples subjected to different pasteurization treatments (72°C/15 s, 76°C/15 s and 80°C/10 s). An apparent increase in the level of caseins was observed along with a decrease in the serum protein contents at pasteurization temperatures of 76 and 80°C. This change can be partly justified by the interactions between β‐lactoglobulin and K‐casein in pasteurized milk. The fat content, viscosity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…It has been reported that the NPN content of the heattreated milk did not change if the heat treatment was maintained between 72-80°C [23]. According to our data, there was no signi cant change of TP and NPN contents IAP but TP contents steadily declined during the prolong storage at 4°C.…”
Section: Parametersupporting
confidence: 56%
See 2 more Smart Citations
“…It has been reported that the NPN content of the heattreated milk did not change if the heat treatment was maintained between 72-80°C [23]. According to our data, there was no signi cant change of TP and NPN contents IAP but TP contents steadily declined during the prolong storage at 4°C.…”
Section: Parametersupporting
confidence: 56%
“…erefore, reductions of fat content in goat milk with increasing heat treatments related to the inde nite change the nature of fat globules and/or enhance lipase activity due to mesophilic activity of stored milk ( Figure 3). In contrast to that, Garcia et al [23] have reported that fat content, viscosity and density of goat milk showed minimal sensitivity to the pasteurization of 72°C, 76°C, and 80°C with holding times of 15 s and 10 s. is study revealed that fat content and viscosity of pasteurized goat milk were sensitive to the pasteurization temperature 72-81°C than holding time of 15-25 s. Fat content of the tested goat milk samples showed higher values than the bovine fat content of the Sri Lanka standards [2].…”
Section: Percentage Of Total Fatmentioning
confidence: 84%
See 1 more Smart Citation